TYPES OF DEIXIS USED IN THE DOUM-TREE OF WAD HAMID: A CORPUS-BASED STUDY - Elbadri Abbas Elzubier (Universitas Islam Sumatera Utara, 2022)
In linguistics, the term deixis is used to describe the use of general words and phrases by speakers to point to persons, objects, specific place and time from their physical or psychological positions while communicating their messages. Such words and phrases are considered deictic when their denoted meaning becomes context-dependent. The present study used AntConc v.3.5.9 corpus analysis toolkit to find out the frequent occurrence of the types of deixis used in the English translation of the short story The Doum-tree of Wad Hamid, and then utilized the useful information obtained along with examples manually derived from the story to discuss the extent to which this use of deixis reflects the author's style and the story's point of view. The results indicated that the common five types of deixis were used in the short story with a different degree of frequency and usage, but personal deixis was the most dominant with 653 examples represented 54.10% out of the total of 1207 deictic instances found in the corpus. Social deixis ranks second with 242 examples represented 20.05%. The study deduced that the dominant use of person pronouns as personal deixis or relational social deictic words reflects the author's style and point of view in the narration line via which the narrator recounts the events from his own perspective.